2020
DOI: 10.7759/cureus.10424
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Cardiovascular Morbidities: A Review Article

Abstract: In obstructive sleep apnea (OSA), there are brief episodes of partial or total upper airway obstruction during sleep, which leads to apnea or hypopneas. Much attention is required to understand OSA's effects on the human body, owing to how common but under-diagnosed this disorder remains. Though the role of OSA in cardiovascular (CV) disease is commonly discussed, it remains unclear how it induces changes in the human body. The intermittent and recurrent hypoxia occurring at the cellular level in this conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 41 publications
0
25
0
1
Order By: Relevance
“…18 Both patients with sleep apnea and those with primary aldosteronism are at increased risk for cardiovascular disease. [19][20][21][22] Although observational studies have shown continuous positive airway pressure use to be associated with improved cardiovascular outcomes in sleep apnea patients, an international, randomized controlled trial failed to demonstrate a reduction in cardiovascular events with continuous positive airway pressure use. 23 The authors hypothesized that this lack of efficacy may have been due to insufficient adherence.…”
Section: Discussionmentioning
confidence: 99%
“…18 Both patients with sleep apnea and those with primary aldosteronism are at increased risk for cardiovascular disease. [19][20][21][22] Although observational studies have shown continuous positive airway pressure use to be associated with improved cardiovascular outcomes in sleep apnea patients, an international, randomized controlled trial failed to demonstrate a reduction in cardiovascular events with continuous positive airway pressure use. 23 The authors hypothesized that this lack of efficacy may have been due to insufficient adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, upper airway anatomy and collapsibility remain a fundamentally important pathophysiological factor. However nonanatomical factors, such as impaired muscle responsiveness, low arousal threshold, high loop gain, rostral fluid shifts, lung volume, additionally play a variable role [ 55 , 56 ]. Recent focused studies in murine models and in humans indicate that IH mediates some of its detrimental effects through adipose tissue inflammation and dysfunction [ 1 , 20 , 28 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Moderate to severe forms of OSA (AHI ≥15) are prevalent amongst men and women aged between thirty-and 70-year old at percentages of 13% and 6%, respectively. 6…”
Section: Risk Factors Of Osamentioning
confidence: 99%